Absurdity in the Literary Works of Albert Camus and Samuel Beckett - Shobeiri, Ashkan (2011)
This research has a focus to reexamine and hence reevaluate the concept of the absurd, philosophically and separately, through selected works of Albert Camus’s The Outsider and The Myth of Sisyphus, and Samuel Beckett’s Waiting for Godot and Endgame. In this attempt, I clarify how the two authors represent the absurdity of the human condition. Moreover, this study directs much of its attention on the comparison between Camus’s and Beckett’s absurdism, in order to elicit more differences than similarities regarding the absurd. Through identification of a gap which indeed appears from comparison of their selected literary works, it becomes possible to renew essential ideas and concepts that the two authors have ventured into. Although the absurdity and meaninglessness of life are both to be found in the oeuvres of Camus and Beckett, yet their conclusions of the issue are different. What differentiates their absurdism is the message that the absurd carries on in their oeuvres, regarding the question of why awareness of the absurd emerges differently in their stories’ characters. While Camus’s characters are happy and courageously accept their destiny, along with their awareness of the absurdity of the world, Beckett’s characters are hopeless and helpless. While Beckett leaves his audience in the dark well of the absurd, Camus shows a path to his readers to move forward and not stay in the dark. By way of offering conclusion, it is possible to be inspired by the absurd to appreciate life. As Camus leaves Sisyphus at the foot of the mountain, it is an absurd man who makes the absurdity of his existence meaningful by creating his own meanings. By dealing with Camus’s absurdism, one is being guided in how the absurd can help one have a more profound vision and understanding of one’s very own existence and a realistic function in our new world.